Microbial reduction of graphene oxide by Lactobacillus plantarum - (:unkn) unknown (Iranian Nano Society, 2019)
Here, we report that the reduced graphene oxide nanosheets were successfully synthesized using the Lactobacillus plantarum biomass in a simple, environmentally friendly and scalable manner. We produced graphene oxide by oxidization and exfoliation of graphite flakes with modified Hummer's method and then reduced to reduced graphene oxide by using Lactobacillus plantarum biomass as a reducing agent. Samples were characterized using Fourier transform infrared spectroscopy, X-ray photoelectron spectroscopy, transmission electron microscopy, scanning electron microscopy, microconfocal raman spectroscopy and thermogravimetric analysis. After the reduction, we observed that a considerable decrease in the oxygen containing functional groups of graphene oxide and an increase in C/O ratio from 1.7 to 3.3 in which confirms sp2 graphitic carbons increase. Mainly, we observed a significant decrease in epoxy and alkoxy functionalities. Furthermore, we determined an exfoliation of graphene oxide to one or several (2-5) layers after the complete reduction. In addition to reducing potential, Lactobacillus plantarum biomass also plays an important role as stabilizing agent; here the reduced graphene oxide showed a good stability in water. The green synthesis reported in this work is concerned with the production of high purity water-dispersible reduced graphene oxide using Lactobacillus plantarum CCM 1904. © 2019, International Journal of Nanoscience and Nanotechnology.
Keywords: 2D material; Graphene; Lactobacillus; Microbial reduction